2016
DOI: 10.1002/aoc.3583
|View full text |Cite
|
Sign up to set email alerts
|

New bioactive Pt(II) binary and ternary metal complexes with guaifenesin drug: Synthesis, geometrical structure, and spectroscopic and thermal characterization

Abstract: Three new binary and ternary metal complexes of Pt(II) with guaifenesin (GFS) drug have been prepared by chelation to guaifenesin ligand (as primary ligand) and glycine amino acid (HGly) and 1,10‐phenanthroline (1,10‐Phen) (as secondary ligands). Characterization was conducted based on elemental analysis, molar conductance, infrared (IR) spectroscopy, thermogravimetric analysis and X‐ray diffraction. The complexes were found to have the formulae [Pt(GFS)2]⋅3H2O (1), [Pt(GFS)2(Gly)]Cl⋅H2O (2) and [Pt(GFS)2(Phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…The TGA plot of 1 displayed four decomposition steps. The first step occurred in the range 30–115 °C with a weight loss of ca 16.14% (calcd 16.68%) due to the release of three molecules of H 2 O and one of HCl . The second step occurred in the range 115–375 °C with a weight loss of ca 18.05% (calcd 18.07%) attributed to the loss of C 6 NH 4 O 0.5 molecule.…”
Section: Resultsmentioning
confidence: 99%
“…The TGA plot of 1 displayed four decomposition steps. The first step occurred in the range 30–115 °C with a weight loss of ca 16.14% (calcd 16.68%) due to the release of three molecules of H 2 O and one of HCl . The second step occurred in the range 115–375 °C with a weight loss of ca 18.05% (calcd 18.07%) attributed to the loss of C 6 NH 4 O 0.5 molecule.…”
Section: Resultsmentioning
confidence: 99%
“…Docking methodology aims to predict the experimental binding modes and affinities of small molecules within the binding sites of particular receptor targets and is currently used as a standard computational tool in drug design for lead compound optimization and in virtual screening studies to find novel biologically active molecules. The basic tools of a docking methodology include a search algorithm and an energy scoring function for generating and evaluating ligand poses.…”
Section: Introductionmentioning
confidence: 99%
“…The minimum energy docked pose revealed that GFV ligand fitted into the curve contour of the targeted protein in the groove. Moreover, GFV ligand acted as strong hydrogen bond acceptor and was engaged in hydrogen‐bonding interactions with nitrogen atom of glycine amino acid (Figure c and Table ).…”
Section: Resultsmentioning
confidence: 99%
“…In order to incorporate the effect of solvent around the molecule, the time‐dependent DFT method (along with LANL2DZ basic set) was used to calculate the electronic absorption spectra of the ligand. The contributions of molecular orbital to highest occupied molecular orbital (HOMO) and lowest occupied molecular orbital (LUMO) were also calculated …”
Section: Methodsmentioning
confidence: 99%